Improving the Quality of Students' Religious Psychology Through School-Based Management Systems and Islamic Boarding School-Based Management - Suheri Suheri (Civiliza Publishing, Indonesia., 2025)
In the context of education in Indonesia, the psychological aspect of religion is an important dimension that needs to be developed continuously. This study aims to analyze the improvement of students' religious psychology through the implementation of School-Based Management (SBM) and Pesantren-Based Management (PBM), as well as to formulate an integrated model of both systems in strengthening students' religious character. Religious psychology is understood as a psychological dimension reflected in spiritual awareness, religious attitudes, emotional control, and social behavior grounded in religious values. This research employed a descriptive qualitative approach and was conducted at SMK Darul Ulum Rangkasbitung and Al-Hikam Islamic Boarding School Pasir Nangka. Data were collected through observation, in-depth interviews, and documentation, and analyzed using thematic analysis. The findings indicate that SBM has strengths in systematic and structured educational management; However, religious psychological development tends to be formal and less intensive. In contrast, PBM is more effective in fostering students' religious psychology holistically through religious habituation, the exemplary role of the kyai, and a supportive spiritual environment, although it remains limited in formal evaluation and documentation. The integration of SBM and PBM shows strong potential to create a balanced educational management model that combines academic excellence with spiritual depth, thereby enhancing students' religious psychology in a sustainable manner.